CRITICAL DISCOURSE ANALISYS SEBUAH MODEL ANALISIS SOSIAL KRITIS DALAM TEKS MEDIA - Abd Ghofur (IAIN MADURA, 2016)
The word discourse is not only called in discourse analysis of texts media, or rather the communication, but also some disciplines, among others such as psychology, sociology, political or literature and others. Because of the difference in the scope of science, a word that has been popular usually have multiple meanings or different definition as well according to various scientists from the scientific fields above and what is circulating in the community. Discourse is meant here is the analysis of the packaging on the shape of the structure or form of an interview as well as the practices of the communicator. Language here becomes a tool as an intermediary extend the hand of power in the point of politics through the depiction of subjects in which there are the interests of ideology.